Meta-Analysis the Effect of Intrauterine Device Uptake on the Risk of Ectopic Pregnancy in Women of Reproductive Age - Mayaningrum, Yulita Endah; Pamungkasari, Eti Poncorini; Murti, Bhisma (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2021)
Background: Indonesia has a high Maternal Mortality Rate (MMR) and has not met the Millennium Development Goals (MDGs) target. Maternal mortality in Indonesia is caused by bleeding, hypertension, infection with abortion, and prolonged labor. One of the causes of bleeding in the first trimester is ectopic preg